Erratum: Helicobacter pylori adhesin HopQ engages in a virulence-enhancing interaction with human CEACAMs (Nature Microbiology (2016) 2 (16189)) - Javaheri, Anahita; Kruse, Tobias; Moonens, Kristof; Mejias-Luque, Raquel; Debraekeleer, Ayla; Asche, Isabell; Tegtmeyer-Backert, Nicole; Kalali, Behnam; Bach, Nina C.; Sieber, Stephan A.; Hill, Darryl J.; Koeniger, Verena; et al. (Nature Microbiology, 2016)
The original version of this Article contained incorrect labels in Figs 3b and 4e. In Fig. 3b, the second western blot panel should have been labelled 'CEACAM1'. In Fig. 4e, the final two values on the y axis should have read 'I91A' and 'I91T'. All versions of the Article have been updated. We apologize for any confusion this may have caused.
Created from Fastlane, Scopus look-up